Exclusive breastfeeding among mothers in Tripura Sundari rural municipality, Dhading, Nepal - Achhami, Elina (Journal of Chitwan Medical College, 2026)
Introduction: The World Health Organization recommends exclusive breastfeeding (EBF) for the first six months of life. The study aims to conduct an exploratory assessment of EBF practices and associated factors among a sample of mothers in Tripura Sundari rural municipality (TSRM), Dhading, Nepal. Method: A quantitative household survey was conducted in TSRM, enrolling 390 breastfeeding mothers of children aged 6 to 12 months as per the calculated sample, with adjustment for potential incomplete data. Ethical approval was obtained. Data were collected from 27 Aug 2023 to 04 May 2024. Mothers with permanent residency were included, while those unable to communicate due to language barriers or health issues were excluded. Convenience sampling was used to select participants. Questionnaires were administered face-to-face through door-to-door surveys using structured tools. Descriptive and bivariate analyses (x2 test) were performed to examine variables such as the mother’s age, education, occupation, place and mode of delivery, and utilization of antenatal and postnatal care. A p≤0.05 was considered statistically significant. Result: Out of the total 390 mothers, the prevalence of EBF was 232(59.49%). The EBF was significantly associated with maternal age (p-value=0.01), place of delivery (p-value=0.04), and mode of delivery (p-value=0.03). Conclusion: This exploratory study found an EBF prevalence of 59.49% among mothers accessible in TSRM, while not generalizable to the entire municipality due to non-random sampling, this warrants further investigation and can inform local awareness programs.